Self-correction in science: The effect of retraction on the frequency of citations - Anton Kühberger; Daniel Streit; Thomas Scherndl (PLoS ONE, 2022)
We investigate the citation frequency of retracted scientific papers in science. For the period of five years before and after retraction, we counted the citations to papers in a sample of over 3,000 retracted, and a matched sample of another 3,000 non-retracted papers. Retraction led to a decrease in average annual citation frequency from about 5 before, to 2 citations after retraction. In contrast, for non-retracted control papers the citation counts were 4, and 5, respectively. Put differently, we found only a limited effect of retraction: retraction decreased citation frequency only by about 60%, as compared to non-retracted papers. Thus, retracted papers often live on. For effective self-correction the scientific enterprise needs to be more effective in removing retracted papers from the scientific record. We discuss recent proposals to do so.